Pressure Perturbation Studies of Noncanonical Viral Nucleic Acid Structures - Judit Somkuti (MDPI AG, 2021)
G-quadruplexes are noncanonical structures formed by guanine-rich sequences of the genome. They are found in crucial loci of the human genome, they take part in the regulation of important processes like cell proliferation and cell death. Much less is known about the subjects of this work, the viral G-quadruplexes. We have chosen three potentially G-quadruplex-forming sequences of hepatitis B. We measured the stability and the thermodynamic parameters of these quadruplexes. We also investigated the potential stabilization of these G-quadruplexes by binding a special ligand that was originally developed for cancer therapy. Fluorescence and infrared spectroscopic measurements were performed over wide temperature and pressure ranges. Our experiments indicate the small unfolding volume change of all three oligos. We found a difference between the unfolding of the 2-quartet and the 3-quartet G-quadruplexes. All three G-quadruplexes were stabilized by TMPyP4, which is a cationic porphyrin developed for stabilizing the human telomere.